The Effect of Brushing on Surface Roughness of Denture Lining Materials - Luciana Valadares Oliveira, MS;1 Marcelo Ferraz Mesquita, PhD;2 Guilherme (Journal of Prosthodontics, 2007)
The purpose of this study was to test the effect of brushing on surface roughness of two resilient liners (Luci Sof and Sofreliner) compared with an acrylic resin (QC 20).